Patterns of genetic diversity in Phaseolus beans - Schinkel, C.; Singh, S.P.; Gepts, Paul L. (1988)
Progress on the observations regarding genetic variability in some Phaseolus spp. is summarized, based on an analysis of phaseollin and isozime variability. In a group of 270 cv. from Latin America, most of them wild, the variability of 8 loci of isozimes was analyzed. Binding data of 5 of these loci indicate that they are not phaseollin-bound. Greater divergence was found between Meso American (S phaseollin) and Andean (T phaseollin) cv. in many enzimatic loci, since both groups showed contrastive alleles. These data also allow subdivisions within the 2 major gene sets. Among the Meso American cv., those from Central America show the characteristic in the S allele of cathodic peroxidase and in the pattern 2 of diaphorase; the F allele of Mdhl is characteristic of a group of Andean cv. In spite of the absence of genetic binding, a high correlation was found (0.70-0.80) between phaseollin and isozime variability, indicating a barrier for recombining the 2 major gene sets. The genetic variability of phaseollin and isozimes was also examined in 55 wild types and in 8 P. acutifolius cv., from an area between Arizona and Nicaragua. A total of 15 different genotypes was found within the wild cv. and only 1 within the 8 cultivated ones. The decrease in genetic variability induced by domestication indicates the need to emphasize preservation of ancestral wild forms. (CIAT)